The size of the placebo effect of a sports drink in endurance cycling performance - Clark, V. R.; Hopkins, W. G.; Hawley, J. A.; Burke, L. M. (Medicine & Science in Sports & Exercise, 1998)
A 40-km time trial on an air-braked ergometer was performed twice by sub-elite cyclists (M = 46; F = 4). One trial was a water-only condition the other either carbohydrate or placebo. Each group was further randomized according to what they were told was in the drink, carbohydrate or sweetener, or not told anything. When Ss were told they were performing with carbohydrate their performance was highest while there was little difference between the other two conditions. Thus, performance differences were largely related to what the athletes believed to be in the drink rather than its actual content. Implication. Performance differences under fuel-additive conditions are largely due to a placebo rather than a real effect. This could explain why investigations measuring CHO-loading effects often produce insignificant results.